2013
DOI: 10.1063/1.4807610
|View full text |Cite
|
Sign up to set email alerts
|

Cross sections for elastic scattering of electrons by CF3Cl, CF2Cl2, and CFCl3

Abstract: Differential, integral, and momentum transfer cross sections have been determined for the elastic scattering of electrons from the molecules CF3Cl, CF2Cl2, and CFCl3.With the help of a crossed electron beam–molecular beam apparatus using the relative flow technique, the ratios of the elastic differential cross sections (DCSs) of CF3Cl, CF2Cl2, and CFCl3 to those of He were measured in the energy region from 1.5 to 100 eV and at scattering angles in the range 15° to 130°. From those ratios, the absolute DCSs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…These results overall seem to indicate that the TCSs for the homologous compounds C n H 2n+2 do not exactly scale with n and that some other molecular effects must play a role in the positron scattering process with those targets. This result is entirely consistent with work from Sophia University (Hoshino et al, 2013 andKato et al, 2012), which clearly demonstrated the importance of molecular effects in electron-molecule scattering.…”
Section: E Comparison Of the Homologous Series Of Molecules C N H 2n+2supporting
confidence: 90%
“…These results overall seem to indicate that the TCSs for the homologous compounds C n H 2n+2 do not exactly scale with n and that some other molecular effects must play a role in the positron scattering process with those targets. This result is entirely consistent with work from Sophia University (Hoshino et al, 2013 andKato et al, 2012), which clearly demonstrated the importance of molecular effects in electron-molecule scattering.…”
Section: E Comparison Of the Homologous Series Of Molecules C N H 2n+2supporting
confidence: 90%
“…The independent atom model with screening corrected additivity rule (IAM-SCAR) method has had significant use in calculating electron scattering cross sections for a wide variety of molecular targets (see, e.g., Refs. [21][22][23][24][25][26] and over a broad energy (E 0 ) range (typically ∼1-5000 eV). As a consequence, we only précis the key points of that approach here.…”
Section: Atomic Optical Model (Om)mentioning
confidence: 99%
“…The effect of the SCAR corrections is to reduce the contribution of the atomic cross sections when they overlap (i.e., at the lower energies). This approximation has been, however, applied successfully: (1) if the constituent atoms in the target are heavy atoms 23 and (2) if the interaction region is the inner part of each atom for fast electrons large-angle scattering, 7 where the potential field is more or less spherical. Even so, at 200 eV for C 4 F 6 isomers, some deviations are emerging commonly for backward scattering above 90 • , which may be due to the multiple scattering processes in a molecule.…”
Section: A Elastic Dcs Overviewmentioning
confidence: 99%
“…This has allowed us to suggest strong evidence in support of the assertion that atomic-like effects may remain prevalent in what are fundamentally molecular systems. Moreover, Hoshino et al 23 as a result of progressively substituting a Cl-atom in going from CF 4 to CF 3 Cl to CF 2 Cl 2 to CFCl 3 , and to CCl 4 , the undulations in the angular distributions have been found to vary in a largely systematic manner, concluding therefore that the elastic scattering process is dominated by the atomic-Cl atoms of the molecules.…”
Section: B Comparison With the Atomic F-dcsmentioning
confidence: 99%